A Case Report of Calyceal Diverticulum: Differential Diagnosis for Organ-Preserving Operations - Kurkov, Alexandr V.; Pominalnaya, Viktoriya M.; Nechay, Viktor V.; Ratke, Igor A.; Mishugin, Sergej V.; Drobyazko, Alexandr A.; Butenko, Alexandra V.; Fayzullin, Alexey L.; Gomzikova, Ekaterina A. (Frontiers in Surgery, 2021)
Calyceal diverticula and epidermal cysts are extremely rare kidney lesions with unknown etiology and pathogenesis. They have non-specific clinical and radiological picture. Despite the benign nature, sometimes these disorders mimic malignant tumors leading to unjustified nephrectomy. We present a clinical and morphological observation of a multicystic lesion in a 76-year-old patient’s right kidney filled with keratinized masses and imitating a malignant solid tumor. The detailed gross, histological and immunohistochemical (desmin, cytokeratin 7, uroplakin and p63) analyses of the kidney tissue excluded the malignant nature of the lesion. The final differential diagnosis was between an epidermal cyst and calyceal diverticulum with pronounced squamous cell metaplasia of urothelium. The upper pole localization of the lesion, its connection with the pelvicalyceal system through the unobstructed isthmus, the presence of urothelial lining and smooth muscle cells in its wall let us diagnose a calyceal diverticulum type I. Knowledge of the key clinical and morphological features of epidermal cysts and diverticula of the pelvicalyceal system will help the practicing physicians suspect the benign nature of such lesions and perform organ-preserving operations.